A method based on fuzzy logic technique for smoothing in 2D - Çinar, A (Springer-Verlag Berlin, 2004)
This paper describes a novel approach based on fuzzy logic technique for smoothing process on the unstructured meshes in 2D. The proposed method works local on triangulation. Therefore, remeshing does not require. It is known that other smoothing operations such as laplacian smoothing, optimization based smoothing, angle based smoothing, and hybrid smoothing operations work global. That is, in these methods, meshing is achieved, afterwards remeshing is done for smoothing. Whereas, the goal of presented method is to find the best fit location of node while meshing is done. However, remeshing process is avoided.
4th International Conference on Computational Science (ICCS 2004) -- JUN 06-09, 2004 -- Cracow, POLAND